Potential health risks associated with pesticide residues from tomato in Tanzania - Kariathi, Victoria; Kassim, Neema; Kimanya, Martin (Global Journal of Food and Agribusiness Management, 2023)
Tomato contributes the highest percent to the fruit and vegetables consumed in Tanzania. Its high consumption is attributed to the presence of bioactive compounds and vitamins known to prevent non communicable diseases. Pesticides used to control pests and diseases cause direct accumulation of pesticide residues in food. Consumption of pesticide contaminated tomato increases the risk of pesticide exposure. This review is on types of pesticides used in tomato production, health effects of pesticides, levels of pesticide residues in tomatoes, dietary pesticide exposure, awareness on pesticides effects and preventive measures as well as policies governing pesticide use in Tanzania. Clearly, there is evidence of extensive use of pesticides in tomato production, limited knowledge regarding pesticide use, as well as weak regulatory framework for pesticide use. Importantly, levels of pesticide residues in tomatoes consumed in Tanzania exceed the recommended maximum residual limits. In order to assure pesticide safety of food, there is a need to identify and control farmers' practices which are highly associated with pesticide contamination in tomatoes. .